(untitled) (International Seven Journal of Multidisciplinary, 2024)
This article is an excerpt from a master’s research project that investigated the subject of reading in a pedagogy course at a Brazilian federal university. This paper discusses the workshop as the theoretical-methodological research-intervention procedure used in the dissertation in question. Here we present the workshop as a relevant technology with which we research with the subject, and not simply about the subject, in a dialogical scene where researcher and researched are co-authors of the enunciations that result in a new text. The methodology proved to be a way of intervening in the reality being researched, and in our case, a means of re-signifying institutionalized discourses. We conclude that the workshop therefore reaffirms itself as an interventional and transformative research proposal, in which institutionalized discursive practices are re-signified.